SD Peran Zakat Dalam Perekonomian Indonesia: Studi Teoritik Dan Empirik - Deti, Sri (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2024)
Theoretically and empirically it has been proven that zakat has a big role in an economy, where zakat can encourage property owners to be creative in managing their assets, encourage good and correct business, encourage accelerated distribution of income, encourage the growth and development of the real sector, encourage the acceleration of national development, is the main source of state cash, and foster a high work ethic. However, its implementation still has many obstacles, including public awareness of zakat, which still needs to be increased. Apart from that, there is also a need for socialization and education on zakat, strengthening qualified amil or zakat collection workers, maximizing the control and reporting system for national zakat management, and implementing the National Zakat Information System (SIZN) to create professional zakat managers.